Crosstalk between microwave ablation and ferroptosis: The next hot topic? - Yu, Lu; Cheng, Min; Liu, Jie; Ye, Xin; Wei, Zhigang; Xu, Jiamei; Xie, Qi; Liang, Jing (Frontiers in Oncology, 2023)
Microwave ablation has been one form of thermal ablation in treatments for many tumors, which can locally control unresectable tumors. Ferroptosis is iron-dependent cell death caused by the cumulative reactive oxygen species and lipid peroxidation products. Recently, increasing evidence has shown that ferroptosis play a vital role in MWA-induced tumor suppression. In this article, we briefly illustrate the concept of ferroptosis, the related signal pathways and inducers, the basic principle of microwave ablation in killing tumors, and the key molecules released after microwave ablation. Then, we describe the crosstalking molecules between microwave ablation and ferroptosis, and discussed the potential mechanism of microwave ablation-induced ferroptosis. This review explores the therapeutic target of ferroptosis in enhancing the systemic antitumor effect after microwave ablation, providing theoretical support in combinational microwave ablation with pro-ferroptosis therapy.